Suppression of tungsten accumulation during ELMy H-mode by lower hybrid wave heating in the EAST tokamak. (August 2017) - Zhang, L.; Morita, S.; Xu, Z.; Zhang, P.F.; Zang, Q.; Duan, Y.M.; Liu, H.Q.; Zhao, H.L.; Ding, F.; Ohishi, T.; Gao, W.; Huang, J.; et al.
Highlights: In order to study the tungsten behavior in the long pulse discharge, tungsten spectra have been measured at 20–140 Å. The tungsten density, nw, is evaluated from the intensity of tungsten unresolved transition array (W-UTA) in a wavelength range of 45–70 Å. The tungsten accumulation often occurs during the H-mode phase in NBI-heated discharges. When the 4.6 GHz LHW is superimposed on the NBI discharge, the tungsten accumulation is successfully suppressed with increased fELM and the H mode can be steadily maintained for longer period. It is found that the tungsten density during H-mode phase in the LHW discharge is less than one order of magnitude compared to the NBI-heated discharge. The results strongly suggest the use of LHW is one of possible methods toward the steady H-mode discharge. Abstract: EAST tokamak has been equipped with upper tungsten divertor since 2014. The tungsten accumulation has been often observed in NBI-heated H-mode discharges suggesting deleterious tungsten confinement in the plasma core. It causes not only H-L back transition but also plasma disruption in several discharges. Suppression of the tungsten accumulation is therefore the most important issue in EAST to achieve a long pulse H-mode discharge. In order to study the tungsten behavior in the long pulse discharge, tungsten spectra have been measured at 20–140 Å. The tungsten density, nw, is evaluated from the intensity of tungsten unresolved transition array (W-UTA) in a wavelength range of 45–70 Å which is composed of several ionization stages of tungsten, e.g. W 27+ -W 45+ at Te0 ∼2.5 keV). It is found that the tungsten accumulation can be suppressed when the 4.6 GHz LHW with PLHW ∼0.8 MW is superimposed on the NBI phase (PNBI = 1.9 MW). During the superimposed phase the ELM frequency, fELM, increases from ∼30 Hz to ∼60 Hz and the tungsten density is halved compared to the NBI-heated discharge. The H-mode discharge can be thus steadily sustained for longer period. It is found that the nw is a large function of the ratio of LHW power to the total injection power, PLHW /(PLHW +PNBI ), and the nw can be reduced, at least, in an order of magnitude smaller than that in NBI-heated discharges at PLHW /(PLHW +PNBI ) ≥ 0.8. The result strongly suggests a possible way toward the steady H-mode discharge.